Network of Health Governance in the Literature from 2019 to 2022 - María Luisa Quintero Soto; Elisa Bertha Velazquez Rodriguez; Cruz García Lirios (International Journal of Community Service & Engagement, 2023)
Corporate governance is a phenomenon that emerges in response to risk events and is observed in three phases: identity or decision-making for the protection of a group, reputation or perceived effectiveness of the strategy, and image as aversion or institutional propensity to the risks. In this way, the objective of the study was to observe the literature concerning corporate governance in the face of the pandemic, as well as its contrast with the evaluations of experts regarding the literature. A documentary, exploratory and cross-sectional work was carried out with a sample of findings published in sources indexed to institutional repositories. Latindex, Class and Redalyc. The results show that corporate governance was impacted by anti-COVID-19 policies in terms of its image, the subsequent impact on reputation and identity. In relation to the stigma, the conversion of corporate governance in the face of the pandemic is explained.